Improved thermooxidation and sedimentation stability of covalently-coated carbonyl iron particles with cholesteryl groups and their influence on magnetorheology - Mrlík, Miroslav; Ilčíková, Markéta; Pavlínek, Vladimír; Mosnáček, Jaroslav; Peer, Petra; Filip, Petr (Journal of colloid and interface science, 2013)
Sedimentation of particles in magnetorheological suspensions represents a crucial problem that concerns their efficient long-term application in practice. Prepared carbonyl iron (CI) microparticles coated with a low density substance, cholesteryl chloroformate, via a two-step reaction and immersed in silicone oil, exhibit three positive aspects: (1) the CI particle modification increased the compatibility between the particles and the silicone oil resulting in improved long-term stability (reduction in sedimentation); (2) the coating provided the particles with enhanced thermal stability in the oxygen atmosphere; and (3) rheological measurements proved a promising magnetorheological performance at different particle weight fractions.